pH‐Controlled Gliding Motions in Pillar[5]arene‐Containing Molecular Shuttles - Nihed Becharguia; Iwona Nierengarten; Alix Sournia‐Saquet; Emeric Wasielewski; Rym Abidi; Béatrice Delavaux‐Nicot; Jean‐François Nierengarten (ChemistryEurope, 2025)
New pillar[5]arene‐based molecular shuttles incorporating an axle component with two stations, namely a –(CH2)10– chain and a protonable triazole subunit, have been prepared. Detailed spectroscopic investigations supported by density functional theory calculations revealed that gliding motions of the pillar[5]arene occur over the full length of the molecular axle in the protonated state, while such molecular motions are limited over the decyl station in the neutral state. Finally, electrochemical investigations further revealed that the oxidation of the pillar[5]arene moiety of the protonated rotaxane also triggers conformational changes and the oxidized macrocycle is only located over the decyl station.